Descriptive Sensory Analysis of Gluten-Containing and Gluten-Free Chocolate Chip Cookies Available in the Marketplace - Eniola Ola; Victoria J. Hogan; Han-Seok Seo (Foods)
Limited research has systematically compared the detailed sensory profiles of commercially available gluten-containing (C) and gluten-free (F) cookies using trained panelists. This study aimed to develop a comprehensive sensory lexicon for C and F chocolate chip cookies and identify key sensory attributes that differentiate them. Seven professionally trained panelists created a lexicon of 33 attributes spanning aroma, flavor, basic taste, texture, and residual property. Using this lexicon, a descriptive analysis was conducted on 12 C and 12 F cookie samples. Multivariate analysis of variance revealed significant differences between the two groups across the 33 sensory attributes (p < 0.05). A mixed model analysis showed that C cookies had higher intensities of chocolate-related and sweet aroma complex notes, while F cookies exhibited stronger nutty, artificial, and off-note flavors. In terms of texture, F cookies were higher in toothpack and powdery mouthcoat, while C cookies displayed more melt-in-mouth characteristics. Principal component analysis and agglomerative hierarchical clustering revealed three distinct clusters of test samples within both crispy and chewy cookie types, with some F cookies closely aligning with C profiles. These findings, along with the developed lexicon, provide a valuable foundation for enhancing the sensory appeal and quality of gluten-free chocolate chip cookies.